Emotion Regulation in Borderline Personality Disorder: Examining the Consequences of Spontaneous and Instructed Use of Emotion Suppression and Emotion Acceptance when Viewing Negative Films. Issue 5 (December 2013) - Evans, Davy; Howard, Maxine; Dudas, Robert; Denman, Chess; Dunn, Barnaby D
Central to models of Borderline Personality Disorder (BPD) is the notion that dysfunctional application of avoidant emotion regulation strategies results in elevated emotional reactivity. To test this account, participants (N = 87) with varying severity of BPD underwent two negative mood inductions, the first with no particular instructions and the second following suppress or accept instructions. BPD severity was associated with greater negative affect at baseline. While BPD severity was associated with greater avoidance, this did not lead to differential reactivity or recovery when viewing the uninstructed film. Both instructed suppression and acceptance reduced emotional reactivity and accelerated recovery in the second film. While BPD severity did not influence how effectively instructed regulation could manage self- reported affect, those with more marked symptoms were trend less effective at regulating electrodermal response. Overall, these data provide little support for the notion that avoidant regulation strategies might lead to emotional hyper-reactivity in BPD, inconsistent with emotional dysregulation accounts of the disorder.